Crise do masculino e ascenção de discursos autoritários: possíveis afinidades entre o ideal viril e a personalidade autoritária - SATO, Yukimi Mori Mesquita (Universidade Federal do Pará, 2025)
In an attempt to define masculinity, we are generally faced with an inflexible set of attributes necessary for the identification of the subject as a man and which, at least apparently, would confirm a certain universality, being supported especially in the opposition and distancing of identifiers considered feminine. Considering that the characteristics from which men seek to distance themselves are not exclusive to feminine subjectivity, but comprise part of the human experience, the attempt by men to suppress certain emotions may be at the origin of a malaise resulting from this internal conflict which, when projected outwards, has violence as one of its possible expressions. At this point, we evidence the existence of a link between characteristics attributed to the masculine and the ideal constantly reenacted by authoritarian subjects. Thus, we seek to question masculinity sustained by the exercise of virility and established as an invariable standard and, with this, we aim to understand: how does the construction of male subjectivity based on specific ideals such as virility, strength and rationality relate to the growing naturalization of authoritarian manifestations directed at external groups – or out-groups? Does the exercise of a masculinity supported by virile ideals necessarily culminate in an authoritarian character? How may the social changes related to gender that have occurred in recent decades have impacted the male position in society and its attempt to guarantee the security of identity by returning to a virility that remains through time? In view of the aforementioned questions, we undertook a theoretical and bibliographical research, approaching the theories of Sigmund Freud, Jacques Lacan and Theodor Adorno, from which it was possible to infer that both the attempts to homogenize masculinity and the authoritarian massification objectives follow the same unconscious trajectories: they start from the presumption of the possibility of achieving total enjoyment, an imaginary completeness, even if it has to be conquered and maintained by force. It is in this direction that the governing ideals of both spheres are supported by the emphasis on the semblance, on the ritualistic character, since the symbolic would constitute the only sphere capable of sustaining an appearance of completeness. In this way, the search for hegemony, an unquestionable totality, results from the predominance of the phallic signifier as the organizer of social ties, resulting in the categorization and hierarchization of subjects taken as objects of satisfaction of some others who are allocated in positions of dominance.